Risk Aversion, Gender, and Constitutional Change. Issue 3 (September 2015) - Verge, Tània; Guinjoan, Marc; Rodon, Toni
Abstract : Independence movements are today present in several stateless territorially concentrated nations, irrespective of their level of self-government. Among advanced industrial democracies, the stronger secessionist movements are found in Belgium, Canada, Italy, Spain, and the United Kingdom (Keating 1996; Sorens 2005). In the absence of a secession clause in their respective constitutions, a broad array of political parties and civil society groups have mobilized to demand a self-determination referendum as a means to let the citizenry of their territories express their will (Muñoz and Guinjoan 2013). Canada held a referendum on the secession of Quebec in 1980 and 1995. The United Kingdom called a popular vote on Scotland's independence in September 2014. In the Spanish case, Catalonia convoked a consultation in November 2014, although the central government did not recognize its legality.